(untitled) (Global Economic Review: Journal of Economics, Policy, and Business Development, 2026)
This article examines the formation and development of the institutional environment for price competition in the Republic of Uzbekistan amid the transformation of the national economy. It explores the role of government institutions, the legal framework, and regulatory mechanisms in ensuring the effective functioning of competitive markets. Particular attention is paid to the analysis of antitrust legislation, price liberalization policies, and measures to develop market infrastructure.